Direct observation of a deoxyadenosyl radical in an active enzyme environment. Issue 24 (16th December 2016) - Heidinger, Lorenz; Kneuttinger, Andrea C.; Kashiwazaki, Gengo; Weber, Stefan; Carell, Thomas; Schleicher, Erik
Abstract : 5′‐deoxyadenosyl radicals have been proposed as the first common intermediate in the molecular reaction mechanism of the family of radical S ‐adenosyl‐l ‐methionine (SAM) enzymes. However, this radical species has not yet been directly observed in a catalytically active enzyme environment. In a reduced and SAM‐containing C140A mutant of the spore photoproduct lyase from Geobacillus thermodenitrificans, a mutant with altered catalytic activity, we were able to identify an organic radical with pronounced hyperfine structure using electron paramagnetic resonance spectroscopy. Guided by quantum‐chemical computations at the density functional theory level of theory, this radical could be tentatively assigned to a deoxyadenosyl radical, which provides first experimental evidence for this intermediate in the reaction mechanism of radical SAM enzymes. Abstract :